Male Sexual Dysfunctions in the Infertile Couple–Recommendations From the European Society of Sexual Medicine (ESSM) - Paolo Capogrosso, MD, FEBU; Christian Fuglesang S. Jensen, MD, PhD; Giulia Rastrelli, MD, PhD; Josep Torremade, MD; Giorgio I. Russo, MD, PhD; Amr Abdel Raheem, MD; Anders Frey, MD; Mikkel Fode, MD PhD, FECSM; Mario Maggi, MD; Yacov Reisman, MD, PhD; Carlo Bettocchi, MD; Giovanni Corona, MD (Sexual Medicine, 2021)
ABSTRACT: Introduction: Sexual dysfunctions (SDs) have been frequently reported among male partners of infertile couples due to psychogenic, relational and/or organic issues related with the inability to conceive. Likewise, male infertility (MI) could be a consequence of sexual dysfunctions. Aim: To review the evidence on the prevalence and treatment of male SDs in men of infertile couples and provide clinical recommendations on behalf of the European Society of Sexual Medicine (ESSM). Methods: The MEDLINE database was searched in September 2019 for randomized clinical trials (RCTs), meta-analyses and open-label prospective or retrospective studies investigating the presence of erectile dysfunction (ED) and/or ejaculatory dysfunctions (EjDs) and/or low sexual desire (LSD) in conjunction with infertility. Main Outcome Measure: The panel provided statements on: (i) Prevalence and association between SDs and MI; (ii) Treatment of male SDs in men of infertile couples. Results: ED has been reported in 9% to 62% of male partners of infertile couples, with severe impairment observed in only 1% to 3% of ED cases. Moreover, worse semen parameters have been associated with greater ED severity. Phosphodiesterase type 5 inhibitors (PDE5is) can be safely used to treat ED among patients seeking fatherhood. Male partners of infertile couples are at higher risk of premature ejaculation (PE). Retrograde ejaculation (RE) and anejaculation are a cause of MI and can be managed with electroejaculation (EEJ) or penile vibratory stimulation (PVS) or, alternatively, with oral treatments, however the latter with limited documented success. Low sexual desire has been reported by one third of men of infertile couples. Conclusion: ED could significantly affect male partners of infertile couple; PDE5is should be suggested to ensure an effective and satisfactory sexual relationship of the couple. Anejaculation and RE should be considered as a possible cause of MI and treated accordingly. Low sexual desire is frequently reported among men of infertile couple and could be a symptom of other systemic conditions or psychological distress. Capogrosso P, Jensen CFS, Rastrelli G, et al. Male Sexual Dysfunctions in the Infertile Couple–Recommendations From the European Society of Sexual Medicine (ESSM). J Sex Med 2021;9:100377.